HOSTILITY, ANGER AND AGGRESSION: PHYSIOLOGICAL DIFFERENCES IN A SAMPLE OF UNIVERSITY WOMEN FROM NORTHERN MEXICO - Lozano Ramírez, Dora Isabel (Universidad Autónoma de Tamaulipas, 2018)
The present study was conducted to determine if there were physiological differences between college women who scored high and those who scored low on a scale measuring hostility, anger and aggression during a non-harassing task.  Measurements of heart rate, skin conductance (SCL), and respiratory sinus arrhythmia (RSA) were taken during a task designed to elicit anticipatory fear.  To measure aggression and its three components, Buss and Perry’s Aggression Questionnaire was used (1992).  The results show that there was a significant difference in RSA (F(7,58)=2.225, p=.45, ?2= .212).   These results suggest that hostile women have low levels of parasympathetic activity prior to the periods of stress, and they are important because they indicate that the physiological differences between hostile and non- hostile women can emerge even with tasks with low levels of provocation.